Outsourcing justice?. (29th May 2018) - Stafford, Anne; Stapleton, Pamela
Abstract: The paper takes an institutional logics theoretical approach to examine how an outsourcing scandal of overcharging for electronic monitoring of offenders was managed so that, despite public outrage, government was able to maintain its outsourcing policies. Using secondary data archival sources in the public domain, it examines the actions of the contractors and state agencies. The paper shows how organisations with different logics became co‐dependent and worked together to resolve the scandal. Market logics were temporarily reined back and state logics emphasised as the contractual environment was stabilised. But ultimately their purpose was protection of the markets logics‐driven policy.